PENGEMBANGAN BAHAN AJAR MATEMATIKA BANGUN RUANG SISI DATAR BERBASIS INQUIRY UNTUK SISWA SMP - Nila Kesumawati; Anggria Septiani Mulbasari; Darmawijoyo Darmawijoyo (Jurnal Dosen Universitas PGRI Palembang)
Abstract: This study aims to produce a teaching material for three dimensional spaces using inquiry based approach. This research is a developmental research consists of three steps: preliminary, formative study (self evaluation, expert review, one to one and small group) and a field test. The subjects were eighth grade student of SMPN 45 Palembang. Experts review suggest that this study has produced a valid and practical teaching material for three dimensional apaces. The results of the field test alsoshow that the material has a potential effect to improve students critical thinking skills. Keywords: Inquiry based approach, three dimensional spaces, worksheet.